An improved suppression subtractive hybridization technique to develop species-specific repetitive sequences from Erianthus arundinaceus (Saccharum complex) - Fan Yu; Yongji Huang; Ling Luo; Xueting Li; Jiayun Wu; Rukai Chen; Muqing Zhang; Zuhu Deng (BMC Plant Biology, 2018)
Abstract Background Sugarcane has recently attracted increased attention for its potential as a source of bioethanol and methane. However, a narrow genetic base has limited germplasm enhancement of sugarcane. Erianthus arundinaceus is an important wild genetic resource that has many excellent traits for improving cultivated sugarcane via wide hybridization. Species-specific repetitive sequences are useful for identifying genome components and investigating chromosome inheritance in noblization between sugarcane and E. arundinaceus. Here, suppression subtractive hybridization (SSH) targeting E. arundinaceus-specific repetitive sequences was performed. The five critical components of the SSH reaction system, including enzyme digestion of genomic DNA (gDNA), adapters, digested gDNA concentrations, primer concentrations, and LA Taq polymerase concentrations, were improved using a stepwise optimization method to establish a SSH system suitable for obtaining E. arundinaceus-specific gDNA fragments. Results Specificity of up to 85.42% was confirmed for the SSH method as measured by reverse dot blot (RDB) of an E. arundinaceus subtractive library. Furthermore, various repetitive sequences were obtained from the E. arundinaceus subtractive library via fluorescence in situ hybridization (FISH), including subtelomeric and centromeric regions. EaCEN2-166F/R and EaSUB1-127F/R primers were then designed as species-specific markers to accurately validate E. arundinaceus authenticity. Conclusions This is the first report that E. arundinaceus-specific repetitive sequences were obtained via an improved SSH method. These results suggested that this novel SSH system could facilitate screening of species-specific repetitive sequences for species identification and provide a basis for development of similar applications for other plant species.